Escherichia col Resistance in Type 2 Diabetes Mellitus with Urinary Tract Infection (UTI) - Shalgam, Dhamyaa Obaid; Al-Tamimi, Baydaa Ali Abd Alwan; Dhaif, Safiya Saad; Salman, Shaima Basil; Salman, Isam Noori (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
The Latin and Greek words "diabetes" and "mellitus," respectively, signify sweet and siphon. Diabetes mellitus (DM) is a metabolic disease marked by abnormally elevated blood glucose levels. DM can be divided into two categories: types 1 and 2. T2DM is hypothesized to affect middle-aged and older individuals who have maintained hyperglycemia as a result of bad eating habits and lifestyle choices. 45 urine samples from diabetics with UTIs of different ages were gathered for this study at the National Diabetes Center of Al-Mustansiriyah University in Baghdad Province, Iraq, between October 2023 and February 2024. The samples were handled carefully in the laboratory utilizing the right protocols to avoid any contamination. To categorize bacterial species in the urinary tract, biochemical assays, the standard urine culture (SUC), and other techniques were employed (cultural characteristics, vitek2 system). E. coli made up 67% of the bacteria that were identified from the urine of T2DM patients who had UTIs. In this investigation, E. coli displayed a high percentage of sensitivity to Nitrofurantoin, Erythromycin, Tetracycline, Oxyacillin, Vancomycin, Teicoplanin, and Imipenem (97%) but resistance to Moxifloxacin, Meropenem, Tigecyclin, Ampicillin, Cefazolin, Ceftriaxone, Ertapenem, Cefoxitin, and Nalidixic acid with rate of 100%.